Mic it! : microphones, microphone techniques, and their impact on the final mix - Corbett, Ian, 1972- (Burlington, MA : Focal Press, 2015)
"Capture great sound in the first place, and spend less time "fixing it in the mix" with Ian Corbett's Mic It! Microphones, Microphone Techniques, and Their Impact on the Final Mix. With his expert guidance, you'll quickly understand essential audio concepts as they relate to microphones and mic techniques, and learn how to apply them to your recording situation. Whether you only ever buy one microphone, are equipping a studio on a budget, or have a vast selection of great mics to use, you'll learn to better use whatever tools you have. Mic It! gives you the background to design and discover your own solutions to record the best sound possible. The information in these pages will help you record great source tracks that can be easily developed into anything from ultra-clean mixes to huge, organic soundscapes"--
Includes index.
Keywords: Microphone; Sound -- Recording and reproducing